The articulation of /ɹ/ in New Zealand English. (28th December 2020) - Heyne, Matthias; Wang, Xuan; Derrick, Donald; Dorreen, Kieran; Watson, Kevin
Abstract : This paper investigates the articulation of approximant /ɹ/ in New Zealand English (NZE), and tests whether the patterns documented for rhotic varieties of English hold in a non-rhotic dialect. Midsagittal ultrasound data for 62 speakers producing 13 tokens of /ɹ/ in various phonetic environments were categorized according to the taxonomy by Delattre & Freeman (1968 ), and semi-automatically traced and quantified using the AAA software (Articulate Instruments Ltd. 2012 ) and a Modified Curvature Index (MCI; Dawson, Tiede & Whalen 2016 ). Twenty-five NZE speakers produced tip-down /ɹ/ exclusively, 12 tip-up /ɹ/ exclusively, and 25 produced both, partially depending on context. Those speakers who produced both variants used the most tip-down /ɹ/ in front vowel contexts, the most tip-up /ɹ/ in back vowel contexts, and varying rates in low central vowel contexts. The NZE speakers produced tip-up /ɹ/ most often in word-initial position, followed by intervocalic, then coronal, and least often in velar contexts. The results indicate that the allophonic variation patterns of /ɹ/ in NZE are similar to those of American English (Mielke, Baker & Archangeli 2010, 2016 ). We show that MCI values can be used to facilitate /ɹ/ gesture classification; linear mixed-effects models fit on the MCI values of manually categorized tongue contours show significant differences between all but two of Delattre & Freeman's (1968 ) tongue types. Overall, the results support theories of modular speech motor control with articulation strategies evolving from local rather than global optimization processes, and a mechanical model of rhotic variation (see Stavness et al. 2012 ).